2013
DOI: 10.1371/journal.pone.0061504
|View full text |Cite
|
Sign up to set email alerts
|

The Cost Effectiveness of Pandemic Influenza Interventions: A Pandemic Severity Based Analysis

Abstract: BackgroundThe impact of a newly emerged influenza pandemic will depend on its transmissibility and severity. Understanding how these pandemic features impact on the effectiveness and cost effectiveness of alternative intervention strategies is important for pandemic planning.MethodsA cost effectiveness analysis of a comprehensive range of social distancing and antiviral drug strategies intended to mitigate a future pandemic was conducted using a simulation model of a community of ∼30,000 in Australia. Six pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 61 publications
5
38
0
1
Order By: Relevance
“…Then, we use an EMR-based dataset capturing ILI incidence from 884 ZIP ( postal) codes and 12 age classes across the USA to rank the relative importance of the various age groups in the transmission of the autumn wave of the 2009 A/H1N1pdm influenza pandemic in that country. We conclude that school-aged children (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) year-olds) were disproportionately responsible for transmitting influenza to infants through working-age adults in the autumn of 2009, in broad agreement with other findings. Our work demonstrates that STE could serve as an important tool for the detailed epidemiological analysis of age structure, especially as EMR data become more prevalent.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Then, we use an EMR-based dataset capturing ILI incidence from 884 ZIP ( postal) codes and 12 age classes across the USA to rank the relative importance of the various age groups in the transmission of the autumn wave of the 2009 A/H1N1pdm influenza pandemic in that country. We conclude that school-aged children (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) year-olds) were disproportionately responsible for transmitting influenza to infants through working-age adults in the autumn of 2009, in broad agreement with other findings. Our work demonstrates that STE could serve as an important tool for the detailed epidemiological analysis of age structure, especially as EMR data become more prevalent.…”
Section: Introductionsupporting
confidence: 89%
“…STE is positively associated with reporting rates, which can partially confound estimates of asymmetric transmission. STE estimates from ILI time-series data from July-December 2009 in the USA suggest that the transmission of the autumn wave of the A/H1N1pdm pandemic influenza outbreak was likely dominated by [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] year-olds. It is unlikely that this result can be explained by differences in reporting rates alone.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Analyses also suggest that school closure combined with the use of antiviral agents is cost-effective and is a justifiable strategy for mitigating influenza pandemics. 23,24 There is, however, a lack of empirical evidence on the effect of school closure on HFMD transmission: one exception is a review of HFMD in Hong Kong that revealed fewer HFMD consultations than expected during the 2003 severe acute respiratory syndrome and the 2009 influenza pandemic, which was attributed to various control measures including school closure. 25,26 This article aimed to assess the effect of school closure on HFMD transmission.…”
Section: Introductionmentioning
confidence: 99%
“…10,14 Yet, analysis suggests school closures are deemed cost-effective and justifiable only in response to highseverity epidemics. [15][16][17] The effectiveness of school closures as a social distancing measure was dependent on socio-economic and geographic contexts, 11,18,19 single versus multi-wave epidemics, 20 and compliance with limiting social interaction during school closures. 11,17,19 Indirect evidence for the effect of school closure on HFMD comes from Hong Kong, where closures during SARS (2003) and pandemic influenza (2009) led to fewer consultations for HFMD than expected based on the preceding years.…”
Section: Context: Global Hfmd Policiesmentioning
confidence: 99%